The prevalence of avian malaria in the migratory birds of Aras - Iğdır region - Dikmen, Meltem. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2016., 2016)
Avian malaria parasites spread throughout the world and affect a vast range of bird species. Plasmodium and Haemoproteus that cause avian malaria are popular models to study the ecology and evolution of parasite-host-vector interactions in the world. The studies on avian malaria have focused mostly on the avians host and the malaria parasites. Avian malaria is also a common infection amongst endemic and migratory birds. Malaria infection might cause rapid population declines or species extinctions as a result of the environmental changes and man-made activities. Trying to understand certain aspects of avian malaria such as the extent of parasite diversity, distribution and prevalence in host populations in Aras-Iğdır region, a migratory hotspot in eastern Turkey, comprise the main objectives of this thesis. For these purposes, the prevalence of Plasmodium and Haemoprateus were confirmed through PCR-based testing. We screened a total of 401 blood samples belonging to 58 bird species of 25 different families. 15 samples were identified as positive and 13 clean chromatograms of a 215 bp cytochrome b fragment of Plasmodium and Haemoprateus sequences were analyzed together with sequences from the MalAvi database. 13 lineages of Plasmodium and Haemoprateus from seven bird genera corresponded to nine haplotypes, all of which were previously not recorded. Except one Plasmodium sample, all samples clustered into the Haemoproteus clade, showing the higher prevelance of the latter in the samples from Aras-Iğdır region. The study results also showed that age-related patterns in avian malaria infections were consistent with the previous studies, where disease survival rates were highers for juveniles, when compared to adults. As a final analysis, we investigated the correlations between infections and three life history characteristics; migratory status, age, and body. The results suggest that age was a significant predictor of overall parasite presence.
Keywords: Avian malaria -- Iğdır.; Birds -- Migration.; Birds -- Parasites.